The effectiveness of universal design for learning (UDL)-based counselling guidance programs on the social-emotional readiness of early childhood children to elementary school early childhood children for elementary school - Sean Marta Efastri; Meta Silfia Novembli; Suharni; Devi Afriyuni Yonanda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Social-emotional readiness constitutes a fundamental prerequisite for the successful transition of early childhood children to elementary school. The inherent limitations of conventional guidance and counselling approaches in accommodating the diverse learning profiles of children trigger the need for a more inclusive intervention model. This research examined the effectiveness of a counselling guidance program based on Universal Design for Learning (UDL) in enhancing children's social-emotional readiness. The study employed a one-group pre-test and post-test design with 30 children aged 5-6 years as subjects. The UDL intervention was implemented over 12 sessions, focusing on the three principles: Representation, Action and Expression, and Engagement. Social-emotional readiness was measured using the Social-Emotional Readiness Scale (SKSE) completed by teachers and the Child Behaviour Observation Sheet (LOPA). Data analysis was conducted using the Paired Samples t-test and the effect size calculation (Cohen's d). The t-test results showed a statistically highly significant increase in scores for both instruments (SKSE: t (29) = 9.22, p<0.001; LOPA: t (29) = 11.55, p<0.001). The effect size (Cohen's d) was considerable (SKSE: d=1.95; LOPA: d=2.44), indicating a substantial practical impact of the intervention. This significant improvement confirms that the UDL-based counselling guidance program, through its multimodal flexibility, effectively enhances emotional regulation and pro-social behaviour in early childhood children. The practical implication of this finding is that the UDL-based counselling model can be adopted as an inclusive, standard intervention framework to prepare children for the diverse demands of the elementary school environment.